2021
DOI: 10.3390/v13081549
|View full text |Cite
|
Sign up to set email alerts
|

Protein Nucleotidylylation in +ssRNA Viruses

Abstract: Nucleotidylylation is a post-transcriptional modification important for replication in the picornavirus supergroup of RNA viruses, including members of the Caliciviridae, Coronaviridae, Picornaviridae and Potyviridae virus families. This modification occurs when the RNA-dependent RNA polymerase (RdRp) attaches one or more nucleotides to a target protein through a nucleotidyl-transferase reaction. The most characterized nucleotidylylation target is VPg (viral protein genome-linked), a protein linked to the 5′ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 166 publications
(263 reference statements)
0
3
0
Order By: Relevance
“…In this process, 3D pol catalyzes the covalent attachment of two uridine monophosphate (UMP) molecules to the hydroxyl group of tyrosine 3 (Y3) of VPg and generates VPg-pUpU-OH, which serves as a primer to initiate the replication process ( 82 84 ). This process has been extensively studied in different members of the Picornaviridae family ( 37 , 85 90 ), and detailed information can be found in this Review ( 90 ). Subsequently, 3D pol catalyzes the synthesis of viral negative- and positive-sense RNA within the replication complex (RC) ( 91 ).…”
Section: Roles Of 3d Pol In Picornavirus Replicationmentioning
confidence: 99%
“…In this process, 3D pol catalyzes the covalent attachment of two uridine monophosphate (UMP) molecules to the hydroxyl group of tyrosine 3 (Y3) of VPg and generates VPg-pUpU-OH, which serves as a primer to initiate the replication process ( 82 84 ). This process has been extensively studied in different members of the Picornaviridae family ( 37 , 85 90 ), and detailed information can be found in this Review ( 90 ). Subsequently, 3D pol catalyzes the synthesis of viral negative- and positive-sense RNA within the replication complex (RC) ( 91 ).…”
Section: Roles Of 3d Pol In Picornavirus Replicationmentioning
confidence: 99%
“…These two studies suggested that the lack of generation of single-stranded viral RNA with an altered CRE was due to the decrease in positive-strand RNA replication, although sufficient negative-strand replication occurred for the generation of a double-stranded RF [ 114 , 115 ]. The extent to which negative-strand initiation is dependent upon the generation of uridylated VPg via the CRE-2C has yet to be resolved [ 47 , 49 , 116 ].…”
Section: A Cis-acting Replication Element (Cre-2c) Plays a Role In Lo...mentioning
confidence: 99%
“…Viral protein genome-linked (VPg) is a small virally-encoded protein that has multifunctional roles in specific steps of some +ssRNA viral lifecycles including viral replication and translation. VPgs are encoded in +ssRNA viral genomes including animal, plant, and fungal RNA viruses and their functions have been primarily studied in picornaviruses, caliciviruses, and potyviruses (1, 2). VPg is covalently linked to the 5’ end of the viral RNA and serves as a primer for both positive- and negative-strand RNA synthesis (3).…”
Section: Introductionmentioning
confidence: 99%